ANALYSIS OF THEORIES OF MYTH AND MYTHOLOGY - Pulatova Sarvinoz Botir kizi; Yusupova Shoira Batirovna (Scholar Express Journals, 2021)
In this article, there is a consideration of theories of myth from antiquity to the 21th century, as well as mythology in Western European literature, in particular in the literature of Great Britain of the 21th century.
Keywords: Myth; Mythology; Language; Linguistics